Pengaruh Kompetensi Aparat Desa Terhadap Kinerja Dan Produktivitas Pegawai Dalam Melayani Masyarakat Desa Studi Kasus Pemerintah Desa Kalisalak - Bayu Erdian Syah; Budi Hartono (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The competence of human resources in the village government is important in building village development and community welfare. The role of village officials is one of the keys to realizing a developed village, considering that village officials are the link between the village community and the government in Indonesia. Therefore, it is important for village officials to have competence and skills so that developments in the central government can be channeled properly and thoroughly to the village community. This study aims to analyze and measure what the effect of human resource competencies on employee performance and productivity is in the case study of the Kalisalak Village government through a qualitative descriptive approach where the analysis method used is using SWOT Analysis, namely Strenght (Strength), Weakness (Weakness) Opportunity (Opportunity) and Threat (Threat). This study found strengths and opportunities that can encourage the improvement of the work of village officials, but also found weaknesses and threats in it. Therefore, it is necessary to apply the right strategy so that the performance and productivity of village officials in serving the community is maintained